Perancangan Aplikasi E-Learning Berbasis Web Pada SMA Martia Bhakti Bekasi - Faris Setiadin; Mira Ziveria (UNIVERSITAS KALBIS, 2022)
Education based on or using the internet is urgently needed. The need for human resources to produce technology-based academic personnel is very urgent. E-Learning is a system or concept of education that utilizes information technology in teaching and learning. In this study, researchers used a prototype research method developed with the PHP and MySQL programming languages ​​for the creation of the database. The purpose of this research is to build a web-based e-learning application that makes it easier to manage assignments, manage subject schedules, and provide material or modules online.